THE ECONOMIC IMPACT OF WAQF ASSET DIGITIZATION ON COMMUNITY EMPOWERMENT AND SOCIAL INVESTMENT - Helma Maraliza (Adisam Publisher, 2025)
This study aims to examine the economic impact of waqf asset digitization on community empowerment and strengthening social investment through a literature review approach. Digital transformation in waqf asset management presents new opportunities for optimizing waqf potential, particularly through increased transparency, efficiency, and accountability in the collection, management, and distribution of benefits to the community. Digitization enables the creation of a more inclusive waqf ecosystem by expanding access to community participation through digital platforms, accelerating the flow of information, and facilitating more structured social investment mechanisms. Based on the synthesis of various studies, waqf asset digitization has been proven to drive local economic growth through financing micro-enterprises, increasing Islamic financial literacy, developing social infrastructure, and enhancing the capacity of beneficiary communities. Furthermore, digitalization also strengthens the role of waqf as a social development instrument by creating a sustainable investment model that can enhance economic independence and community well-being. This study confirms that waqf asset digitization is not merely an administrative modernization but a transformational strategy for promoting community empowerment and more effective social investment.